THE EFFECT OF ATTITUDE AND SPIRITUAL INTELLIGENCE TOWARDS MATH ACHIEVEMENT OF CLASS XI MAN KOLAKA - Rustam Rustam (USN Kolaka, 2016)
The purpose of this research was to determine the effect of the attitude and spiritual intelligence toward mathematics achievement of students of class XI MAN Kolaka. This research was conducted in MAN Kolaka starting from April 27 until May 27, 2015 the second semester of the academic year 2014/2015. Subjects in this study were all students of class XI MAN Kolaka in the academic year 2014/2015, amounting to 104 students consisting of four classes, namely class IPA1 totaling 23 people, IPA2 classnumbering 24 people, IPS1 class numbering 26 people, and the class IPS2 totaling 31 people. The sample taken from the population was 30% or 32 students. This research included in the type of survey research, in which the researcher acted directly for the data retrieval by looking at student achievement and provide a questionnaire attitudes of students and students' spiritual intelligence. Data collection in this study using instrument namely questionnaire for attitude of students consisting of 20 items and spiritual intelligence consisted of 20 items. While the documentation was used to collect data concerned mathematics achievement of students of class XI MAN Kolaka. Data analyzed using descriptive statistics and inferential statistics. Based on the analysis, it was concluded that attitude and spiritual intelligence toward mathematics achievement of class XI MAN Kolaka had no significant positive effect on the mathematics achievement. Wherein the hypothesis testing results showed that the test of thit =0.00005 > Ttable = 3,31 at the significant level.